La grammaire dans les dictionnaires: le cas des verbes - Prandi, Michele (Neophilologica, 2010)
This paper aims at discussing the amount of grammatical information that has to be included into an adequate lexical description of a language and into an ideal dictionary. Unlike classificatory nouns, such relational terms as verbs, adjectives and nouns of events can only be defined on condition that some relevant grammatical and relational properties are taken into account. Against the distinction between punctual and relational concepts, focus will be put on verbs, and the following topics will be illustrated: the distributional concept of use, the different grammatical functions of verbs, valency, lexical solidarities, polysemy.